Modulation of defensive reflex conditioning in snails by serotonin - Andrianov, Vyatcheslav V.; Bogodvid, Tatiana K.; Deryabina, Irina B.; Golovchenko, Aleksandra N.; Muranova, Lyudmila N.; Tagirova, Roza R.; Vinarskaya, Aliya K.; Gainutdinov, Khalil L. (Frontiers in Behavioral Neuroscience, 2015)
We studied the role of serotonin in the mechanisms of learning in terrestrial snails. To produce a serotonin deficit, the “neurotoxic” analogues of serotonin, 5,6- or 5,7-dihydroxytryptamine (5,6/5,7-DHT) were used. Injection of 5,6/5,7-DHT was found to disrupt defensive reflex conditioning. Within two weeks of neurotoxin application, the ability to learn had recovered. Daily injection of serotonin before a training session accelerated defensive reflex conditioning and daily injections of 5-HTP in snails with a deficiency of serotonin induced by 5,7-DHT restored the snail’s ability to learn. We discovered that injections of the neurotoxins 5,6/5,7-DHT as well as serotonin, caused a decrease in the resting and threshold potentials of the premotor interneurons LPa3 and RPa3.